Políticas públicas em educação: o curso de formação de professores do estado de São Paulo - Medeiros, Tiago Batista (Universidade Federal de São Carlos, 2014)
There are some arguments about the importance of education in the formative process of the population, once it can diminish inequalities and to boost the economic, social and cultural development of a nation. High-quality public education is a complex universe which is impossible to understand through a single perspective. Thus, the motivation for this research was the comprehension of what was being practiced in in the bigger public school system of the country. The Curso de Formação Específica (Specific Content Degree Course), an education public policy was offered by Escola de Formação de Professores (EFAP), from 2010 to2012, as the third phase of the public selection that hired teachers for basic education, back in 2010. The selection was part of a program called Programa Mais Qualidade na Escola which integrated other alike programs implemented during José Serra s tenure as a governor in São Paulo, from 2007 to 2010. The referred program was a public policy demanded through a social claim for better education in the state. The Specific Content Degree Course was designed having the official curriculum as basis, which was established considering the data provided by SAEB and ENEM, among other evaluation tests that happened in 2007. The development of the Specific Content Degree Course aimed to provide a better capacitation for newly hired teachers based on the official curriculum. Thus, the main goal of the course was to present the curriculum to the teachers, offering a familiar approach. More importantly, they were presented to the curricular proposal that guided the teaching practice on their specific area. Considering the panorama above, it is important to highlight the proposal here is to analyze and verify if the course achieved the goals proposed by the govern education department. We have analyzed the first experience of the Specific Content Degree Course, considering the perspective of the professionals (EFAP) who conceived it, as well as the perspective of the teachers who attended the course. The analysis of both perspectives is important to verify whether the goals of the course were achieved or not; if it has contributed to the formation of the professionals and, furthermore, if their personal goals were somehow achieved within the course. The purpose of the analysis is to confront these different perspectives in order to understand how this public policy is comprehended by the involved ones. The relation between the mentioned actors and the already referred public policy is called Avaliação de Resultados (Assessment Results) (DRAIBE, 2001) in the Public Policy studies and is also the content of this thesis.
Keywords: Políticas públicas; Qualidade na educação; Professores - formação; Public policy; Quality; Education; CIENCIAS HUMANAS::CIENCIA POLITICA